PENGEMBANGAN WILAYAH BERBASIS POTENSI UNGGULAN DI KABUPATEN MANGGARAI TIMUR PROVINSI NTT SEBAGAI DAERAH OTONOM BARU - Maria Fransiska Darlen; Setia Hadi; M Ardiansyah (Diponegoro University, 2015)
East Manggarai Regency is a new autonomous region of the division of Manggarai Regency in East Nusa Tenggara Province. As a new district, the area must be developed based on the dominant potentials in the region so that the regional government is more flexibel to design appropriate regional development strategy and create a conducive investment climate to attract investors to the area. The purpose of research is to identify potential sectors that can be developed and provide more economic value, evaluating existing landuse based on land capability and formulate East Manggarai District development strategies. The method used is the input-output analysis combined with analysis of LQ, LI, SI and SSA to determine the dominant sectors and leading commodity, image interpretation and analysis of land capability and SWOT analysis to formulate a regional development strategy. The results showed that the leading sectors in East Manggarai district consists ofthe food crops,the manufacturing sector and the non-oil sectorand the trade sector. Based on the ability of the land, there are many areas that are not their designation as the management of extreme farm lands. Thus, it needs the appropriate strategy in the management of the territory through conducive government policies to the development of the leading sectorsEast Manggarai Regency is a new autonomous region of the division of Manggarai Regency in East Nusa Tenggara Province. As a new district, the area must be developed based on the dominant potentials in the region so that the regional government is more flexibel to design appropriate regional development strategy and create a conducive investment climate to attract investors to the area. The purpose of research is to identify potential sectors that can be developed and provide more economic value, evaluating existing landuse based on land capability and formulate East Manggarai District development strategies. The method used is the input-output analysis combined with analysis of LQ, LI, SI and SSA to determine the dominant sectors and leading commodity, image interpretation and analysis of land capability and SWOT analysis to formulate a regional development strategy. The results showed that the leading sectors in East Manggarai district consists ofthe food crops,the manufacturing sector and the non-oil sectorand the trade sector. Based on the ability of the land, there are many areas that are not their designation as the management of extreme farm lands. Thus, it needs the appropriate strategy in the management of the territory through conducive government policies to the development of the leading sectors